Caryological analysis of South american species of Vernonia (Vernonieae, Asteraceae) - Angulo, Maria Betiana (2009)
In the present study 16 populations belonging to 13 species of the genus Vernonia Schreb. were examined cytologically. In total, six different chromosome numbers, which represent three basic numbers: x=10, x=16 and x=17, were found. These results include the ﬁrst chromosome number reports for the following four species: V. lanifera Cristóbal & Dematt. (2n=2x=32), V. membranacea Gardner (2n=2x=34), V. salzmannii DC.(2n=2x=20) and V. scabrifoliata Hieron.(2n=2x=128). Besides, a new chromosome number was found in V. saltensis Hieron. (2n=2x=32), for which only tetraploid populations have been previously recorded. The data obtained in this work, along with the information available from the literature, show that the genus Vernonia in South America is heterogeneous with basic chromosome numbers that range between x=9 and x=19. These numbers suggest that a combination of polyploidy and aneuploidy has played an important role in the evolution of the genus.